Noticeable Bone Degradation on a Plain Radiography: a Case - Jaramillo-Núñez, A.; Sánchez-Rinza, B. E.; Pérez-Meza, M. (Revista Mexicana de Ingenieria Biomedica, 2018)
In this paper, an image of the humeral head obtained from a plain radiography was analyzed. The radiograph was obtained from a forty year-old female with diagnosed breast cancer and discomfort on the right shoulder. The aim of the study was to determine whether it is possible to observe early bone metastasis with plane radiography using the so called scanning method. Plotting the intensity distribution along the rows of the image is a fast, qualitative way to know if the bone has some abnormality. If the curves are “smooth” then the bone is healthy, but if they are discontinuous then it is sick. To obtain quantitative results, the rows intensities were analyzed around discontinuous zones. Using this technique it was possible to observe bone degradations of the order of 11 %.